Perlakuan Pemupukan NPK Untuk Meningkatkan Pertumbuhan Dan Produktivitas Tanaman Rosela - Misnen Misnen; Badawi Badawi; Desy Lusiyana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2019)
Rosella (Hibiscus sabdariffa L) is a herbaceous plant that can thrive in various types of soil, climate, and low water areas. Roselle flower is useful as medicine and food preparation. Palimanan Barat Village is a village that has a potential land area of ??105 ha which is not used. Since 2012 rosella plant has become one of the plants cultivated by the community of Palimanan Barat Village, assisted by CSR from PT Indocement. But the amount of rosella harvest was considered unsatisfactory. In 2019 Indocement's Center for Research, Training and Community Empowerment (P4M) conducted a study to improve the growth and productivity of rosella gardens using different dosage NPK fertilizer treatment methods. The several stages to plant rosella include land management, nursery, basic fertilization, planting, fertilizing, maintaining, observing and harvesting. In the experiments, different treatments were carried out on the NPK amount. There are four trials of NPK administration on rosella plants, namely roselle plants given NPK with the amount of 0 grams, 20 grams, 40 grams, and 60 grams. Through these experiments obtained good quality rosella in the treatment of 40 grams fertilizer. Keywords: NPK Fertilization Treatment, growth and productivity